Treatment of refractory poly articular course juvenile idiopathic arthritis with tofacitinib: Extended experience from Bangladesh. - Kazi Iman; Laboni Akter; Mohammad Masudur Rahman; Kamrul Laila; Mohammad Imnul Islam; Shahana A Rahman (PLoS ONE)
Background Juvenile Idiopathic arthritis (JIA) is one of the most common chronic diseases in children. It still remains a challenge to treat refractory poly-articular course JIA patients, especially in Bangladesh, where patients from low socio-economic backgrounds are unable to manage biological agents. Tofacitinib is one of the alternative options to biological agents, which can be taken orally and is cost effective. The purpose of this prospective observational study was to evaluate the efficacy of tofacitinib in the treatment of refractory poly-articular course JIA cases. Materials and methods This study was carried out in the Department of Pediatrics, Bangabandhu Sheikh Mujib Medical University (BSMMU). A total number of 50 refractory polyarticular course JIA patients received JAK-2 inhibitor, tofacitinib along with other drugs according to the recommended doses. The disease activity level was measured by Juvenile Arthritis Disease Activity Score-27 (JADAS-27). All the cases were assessed at baseline, 6th, 12th and52nd week of tofacitinib therapy. The relevant statistical tests were applied for data analysis. Results After treating the refractory cases with tofacitinib, arthritis subsided, and laboratory parameters improved in all the cases. Overall JADAS-27 score improvement was 40.67%, 56.38% and 96% at 6th, 12th and 52nd week of follow-up respectively. It was also possible to taper the dose of steroid gradually and stopped it by 24 weeks. Tofacitinib was well tolerated with minimum side effects. Conclusions Tofacitinib was effective to all the children with poly-articular course JIA. It was well tolerated and had very few tolerable adverse effects.